Four Types of ST11 Novel Mutations From Increasing Carbapenem-Resistant Klebsiella pneumoniae in Guangdong, 2016–2020 - Zhao, Yunhu; Liao, Yalong; Zhang, Ni; Liu, Suling; Zhang, Jiao; Hu, Xuejiao; Zhou, Dianrong; Deng, Qianyun; Shi, Yanping; Gu, Bing; Hou, Tieying (Frontiers in Microbiology, 2021)
Objectives: This study aimed to explore changes in carbapenem-resistant K. pneumoniae (CR-KP) isolates collected in Guangdong over the period of 2016 to 2020. Methods: Antibacterial susceptibility was quantified through VITEK 2 compact and K-B method. Carbapenemase phenotypes and genotypes were characterized by modified carbapenem inactivation method (mCIM), EDTA-carbapenem inactivation method (eCIM), and polymerase chain reaction (PCR). Molecular characteristics and evolutionary trends were analyzed by multilocus sequence typing and evolutionary tree. Results: A total of 2847 isolates of K.pneumoniae were separated in 2016-2020, and the separate rate of CR-KP increased from 5.65% to 9.90% (P=0.009). The top 3 wards were intensive care unit (ICU) (21.92%), neonatal wards (13.70%), and respiratory wards (12.33%). Serine carbapenemase was the main phenotypes and KPC was the main genotypes in 146 CR-KP strains, in which 57 were contained two resistant genes, 1 was contained three resistant genes. Two polygenic strains were first found: IMP+GES and KPC+NDM+VIM, but all the phenotypes were metalloenzyme, indicated that metalloenzyme was usually the first choice for CR-KP resistance. In addition, all the ST54 of metalloenzyme type contains IMP, and all the ST45, ST37, and ST76 contain OXA. ST11 was the most prevalent (42.47%), a novel type of ST11 mutation, the rpoB was mutated from sequence 1 to sequence 146, was in an independent separate branch on the evolutionary tree, and resistant to all antibacterial agents. The other 3 mutants: rpoB 1 to 15, infB 3 to 148, infB 3 to 80, also resistant to all antibacterials. Notely, all the four mutants produced serine carbapenemase and contained KPC, indicated that the prevalent strain, ST11, has a serious consequence of mutation, will lead to an outbreak with the fully resistant, probably. What’s more, the medical burden of patients with CR-KP infection was far greater than that of carbapenem-susceptible K. pneumoniae (CS-KP). Conclusions: The infection rate of CR-KP has increased, ICU and neonatal wards have become the key infection areas. Producing serine enzyme, KPC genotype and ST11 are the predominant CR-KP. Polygenic strains and ST11 mutation made clinical treatment difficult, may become a potential threat.